pushpitkc wrote:
\((n+k)^2 - 2nk =\)
A. \(n^2 + k^2\)
B. \(n^2\)
C. \(0\)
D. \(n^2 - k^2\)
E. \((n-k)^2\)
My approach would have been the same as that provided by
philipssonicareThat said, we can also solve this problem by
plugging in values and evaluatingHere's what I mean.
If n =
2 and k =
1, then:
(n + k)² - 2nk = (
2 +
1)² - 2(
2)(
1)
= 3² - 4
= 9 - 4
=
5So, when n =
2 and k =
1, (n + k)² - 2nk =
5This means the answer choice that is EQUIVALENT to (n + k)² - 2nk must also equal
5 when n =
2 and k =
1Let's check the answer choices...
A. n² + k² =
2² +
1² =
5 PERFECT - keep
B. n² =
2² =
4. No good. We need
5. ELIMINATE.
C. 0 No good. We need
5. ELIMINATE.
D. n² - k² =
2² -
1² =
3. No good. We need
5. ELIMINATE
E. (n - k)² = (
2 -
1)² =
1. No good. We need
5. ELIMINATE
By the process of elimination, the correct answer is A
Cheers,
Brent
_________________
Test confidently with gmatprepnow.com